The Law Applicable to Security Interests in Intermediated Securities under OHADA Law - Monsenepwo Mwakwaye, Justin (Universität Würzburg, 2022)
In recent decades, the technical handling of custody business in the OHADA region has undergone a lasting change. There has been a shift from a direct to an indirect holding system, in which the interests of an investor in respect of the underlying securities are recorded in the books of an intermediary (such as a bank or a securities firm). Under the law of all states within the OHADA region, the traditional conflict of laws rule for determining the enforceability of a securities pledge that occurs in the indirect holding system is the lex rei sitae (or the lex cartae sitae or the lex situs ) rule. However, the traditional lex rei sitae rule cannot be appropriately applied to a system where the dematerialised securities are held through multiple layers of intermediaries located in different jurisdictions. Yet, until the intermediated system and the collateralisation of intermediated securities in the OHADA region will continue to operate in somewhat legally murky waters, leading to more instability in the financial markets. Therefore, Justin Monsenepwoaims to find an appropriate and consistent approach that reflects the reality of the indirect holding system in the OHADA region. “This publication is essential reading for policy makers, academics, market participants, and legal practitioners in the OHADA region and beyond. I am convinced that its in-depth analysis of OHADA’s substantive and conflict of laws rules will go a long way in filling the gap in this area and encouraging further development in the future.” Christophe Bernasconi, Secretary General of the „Hague Conference on Private International Law“ – HCCH in the foreword
Keywords: Competencia; Competition law

Overcoming Divergence in English and French Contract Law: A Common Taxonomy of Commercial Contracts - Pedamon, Catherine (University of Westminster, 2022)
The works presented for the PhD by publication are all connected in the way they engage in a functionally comparative study of the English and French law responses to common problems pertaining to contractual performance and contractual interpretation. My comparative inquiry demonstrates that both France and England have stayed true to their historic responses in times of peace and crisis confirming different mentalités juridiques. As neither England nor France offers ideal solution, parties may be better off finding a resolution to their disputes beyond the legal realm and respond to calls for collaboration. This nevertheless shows persisting differences in Anglo-French approaches. This thesis however argues that these divergences may nevertheless lead to common results through the lens of a taxonomy of commercial contracts – professionally drafted contracts may lead to converging results given the common application and interpretation of frequently used clauses beyond a domestic legal culture; by contrast, rudimentary contracts produce diverging results as the interpretation of these agreements is marked by a distinctive domestic socio-legal culture. This taxonomy has the potential to improve the predictability of outcomes in commercial disputes in England and France.
Keywords: Commercial contracts; Contract law; England; France

Reforming investor-state dispute resolution: Focusing on the roles of domestic courts - Ma, Wanli (Erasmus University Rotterdam, 2022)
While a universally applicable multilateral agreement on investment is not yet available, a broad network of BITs and investment chapters in FTAs has been put in place to protect foreign investors and their investments. Meanwhile, investment arbitration has become a defining feature of modern international investment law over the recent decades, enabling foreign investors to launch an investment arbitration against host states, often without the need to go through local remedies before that. With the caseload of investment arbitration increasing at a rather rapid speed, such a dispute resolution method has also attracted fierce criticism. Many commentators have alleged, among other, that the decision-making of investment arbitrators has been inconsistent and unpredictable, that investment arbitration has become a threat to public interest, that investment arbitration proceedings are not transparent enough, that the arbitrators involved are not independent nor diverse enough, that the lack of an applellate mechanism compromises the quality of decision-making, and that investment arbitration has become far too costly and time-consuming. Against such a backdrop, the global community has made joint efforts to reform the investment arbitration system, not least through various initiatives developed at ICSID and UNCITRAL. Almost at the same time, national states also seem to have started to reconsider the costs and benefits of including investment arbitration in their investment agreements as a method for the resolution of disputes with foreign investors. Although the caseload of investment arbitration continues to grow and national states keep concluding IIAs containing investment arbitration clauses, at least some countries in their more recent investment treaty making practice have demonstrated a policy trend to rein in investment arbitration and ramp up the role of domestic courts in resolving investment disputes. They often do so by exiting the ICSID system, terminating their investment agreements with economic partners, excluding investment arbitration from their investment agreements, and conditioning investment arbitration upon the prior use of litigation via domestic courts. While the state practice mentioned above surely does not suggest the global society has any intention to abandon investment arbitration any time soon, it prompts us to take a step back and reconsider the role that domestic courts may play in resolving investment disputes, instead of solely focusing on the piecemeal reform of investment arbitration. When it comes to investor-state dispute resolution, domestic courts can indeed play different roles along the process. Like investment tribunals, domestic courts can also adjudicate investment disputes between foreign investors and local authorities. Such a judicial role sometimes is also confirmed in investment agreements through, for example, the exhaustion of local remedies rule, the clause demanding pursuit of local remedies prior to investment arbitration and the fork-in-the-road provision. In the context of non-ICSID arbitration, disputing parties are often entitled to applying for the review by domestic courts loci arbitri of the rulings and awards rendered by investment tribunals. Domestic courts loci arbitri would thus assume a supervisory role with regard to arbitration proceedings and arbitral outcomes, as they may set aside arbitration awards in question according to the review grounds enumerated in local arbitration laws. Moreover, domestic courts in a broader sense may be called upon to support the conduct and / or authority of investment arbitration, by recognizing and enforcing the investment awards rendered by arbitral tribunals and issuing interim measures of a judicial nature to facilitate the arbitration process. Since litigation through domestic courts and investment arbitration are two primary remedies that foreign investors often rely on for the resolution of investment disputes, this study constructs three models of institutional design with regard to the allocation of jurisdiction over investment disputes between domestic courts and investment tribunals. While the reality may turn out to be more complicated, such three models roughly represent the institutional choices facing national states. These three models are: (i) utter reliance on domestic courts as the exclusive forum for investor-state dispute resolution, (ii) investment arbitration operating as a substitute for litigation via domestic courts, and (iii) investment arbitration working as a complement to litigation via domestic courts. In order to conduct a comparative institutional analysis of the three models to reveal their respective tradeoffs, this study employs a goal based approach which is increasingly used to analyze the effectiveness of international adjudicatory mechanisms. As a result of the employment of the goal-based approach, the goals of investor-state dispute resolution are recognized as achieving fair and efficient dispute resolution, promoting state compliance with investment treaty norms, facilitating the objectives of the investment law regime, and legitimizing the underlying investment treaty regime. While the quality of the national judiciaries of many developing countries is not the same as it was decades ago largely due to the judicial reforms launched around the world, fairness and efficiency in dispute resolution still cannot be fully guaranteed in the domestic courts of those countries without a robust legal system and a good record of the rule of law. However, there are certain institutional characteristics of court litigation that may facilitate the efficiency in the resolution of investment disputes, such as the unique advantage of domestic courts that they can work as a single forum for dispute resolution and the better knowledge of court judges of the domestic legal framework at issue. Domestic courts also hold great potential in promoting the compliance by national states with investment treaty norms not least because they have more flexibility in awarding both primary and secondary remedies, but that of course depends on whether domestic courts can adjudicate investment disputes in a fair and impartial manner. Moreover, while utter reliance on litigation via domestic courts may strengthen the domestic rule of law and improve the investment climate in the long term by pressing host states to improve their legal systems and judicial institutions, it may also invite the politicization of investment disputes and the diplomatic intervention from home states in investor-state dispute resolution. Furthermore, despite the risks created for foreign investors, reliance on domestic courts as the exclusive forum may enhance the legitimacy of the investment treaty regime by reducing the sovereignty costs incurred by national states and putting domestic investors and foreign investors on the same footing. Investment arbitration operating as a substitute for domestic courts, on the other hand, demonstrates certain advantages, which are typically affiliated with international arbitration, in achieving the fair and efficient resolution of investment disputes. Unlike domestic courts, which are an integral part of the state apparatus, investment arbitrators are often immune from the influence of domestic politics and are thus believed to be independent and impartial. Meanwhile, the specialization of arbitrators in a particular area of knowledge and the procedural flexibility of arbitration proceedings, among others, are expected to improve efficiency in the resolution of investment disputes. However, empirical evidence presented in the literature sometimes suggests that, in reality, investment arbitrators may not be that unbiased and investment arbitration proceedings often drag on with a bill of a massive amount. Besides, although investment tribunals have a broad scope of jurisdiction over the behavior of different government branches, the practical difficulties they face in awarding primary remedies may damage their ability in promoting state compliance with investment treaty norms. In addition, the introduction of investment arbitration grants to foreign investors a standing in international arbitration proceedings, to a large extent reducing the need for diplomatic protection and home state intervention. However, the positive impact of investment arbitration in facilitating the development of the domestic rule of law and the maintenance and increase of foreign capital is less certain. As for the preservation of the legitimacy of the underlying investment treaty regime, investment arbitration as an alternative to domestic courts cannot be relied on to produce much positive impact. For instance, the increasing sovereignty costs and financial burden imposed on national states would probably prompt more of them to turn against the investment treaty regime. The complement model, in which domestic courts assumes primary jurisdiction and investment tribunals secondary jurisdiction over investment disputes, stands a good chance in keeping the advantages of both court litigation and investment arbitration while avoiding their disadvantages. In the complement model, domestic courts will act as the first line of defense in adjudicating investment disputes, and the institutional advantages of court litigation will be enabled to release their potential. At the same time, even if foreign investors are not satisfied with the judicial outcome or regard the court proceedings as corrupt or unfair, they may escalate the specific disputes to investment tribunals for further consideration. Since court judges are more knowledgeable and experienced in the interpretation and application of domestic law, the legal analysis of court judges will also benefit the decision-making of investment arbitrators in the subsequent arbitration proceeding. Allowing domestic courts to have a first try at investment disputes will also increase the likelihood that primary remedies could be accorded, thus the unique advantages of primary remedies in promoting state compliance with investment treaty norms are not discarded in the complement model. Moreover, the complement model is also more promising in facilitating the achievement of the objectives of the investment treaty regime, and that is because domestic courts are not marginalized in the complement model, the antagonism between foreign investors and host states may be expected to decrease, and the depolicization of investment disputes will not be lost since investment arbitration is kept as an option. Furthermore, the complement model strikes a better balance among the interests of foreign investors, host states and other stakeholders, thus it is more likely to preserve and even enhance the legitimacy of the underlying investment treaty regime than the other two institutional choices. Although the complement model serves the goals of investor-state dispute resolution the best in theory, not any casual combination of court litigation and investment arbitration will do the job; instead, only a smart mix of the two dispute resolution methods can give full play to the advantages of the complement model. Now, we switch to the supervisory role of domestic courts in investor-state dispute resolution. While a systemic appellate mechanism has not been created for investment arbitration, disputing parties may rely on setting-aside proceedings in non-ICSID arbitration to challenge arbitration awards. In other words, domestic courts loci arbitri may conduct a judicial review of the rulings and awards made by investment tribunals. However, a theoretical analysis of the judicial review mechanism supported by empirical evidence has shown that the mechanism has several flaws, which include but are not limited to the points that follow immediately. Since there is only a casual link between the seat of arbitration and the investment dispute, it is inappropriate to subject the decision-making of arbitrators to the judges from the place where the arbitration proceedings took place. The very fact that review courts have been overwhelmingly located within the developed North could raise concern that the judicial review mechanism is inherently biased against developing countries which have already shown a somewhat negative sentiment towards investment arbitration. Given that judicial review proceedings could easily go through more than one instance of court proceedings in many jurisdictions, the dispute resolution process may consume more time and generate higher costs. From this point of view, the judicial review mechanism favors the richer party in investment arbitration and could become a weapon of dilatory tactics available for such a party. Considering the higher error costs relating to investment arbitration than that relating to commercial arbitration, limited review grounds and a copious amount of deference to arbitral tribunals may not prove to be as effective in the scrutiny of investment awards. Moreover, the idiosyncrasies as to review grounds and standards across jurisdictions indicate that inconsistency would also probably permeate the judicial review practices, which would then encourage forum shopping that leads to increased costs and decreased efficiency. In addition, as both review courts and enforcement courts may exercise control over investment awards, the setting-aside decision may be merely disregarded at the enforcement stage and the overall efficiency of investor-state dispute resolution may be reduced. In order to overcome many of the flaws mentioned above, a delocalized form of review should be introduced to take place of the current judicial review mechanism.

Corporate Governance and Women on the Board of Directors : the Legal Framework towards a Minimum Harmonisation in the European Union - Lamy Martin, Joy (Université Paris-Saclay, 2022)
This thesis concerns the recent and considerable change in corporate governance legislation, specifically how boards of directors address the issue of parity and the appointment of its members in public limited companies. This research will challenge European Union law which, to date, does not propose EU harmonization.The UK, France, Germany and Norway (a non-member country but one that will be included in this research) have introduced changes to their national legislation in relation to company boards in public listed companies. This research will focus on a comparative study of parity on company boards under European Union law and its application in the UK (pre-Brexit), Germany, France and Norway. The application of corporate governance codes or soft law and the proposal for a hard law directive demonstrate a fragmentation in the EU, as the application of law by hard quotas divides member states and parliamentarians in European Union law. Corporate governance law in the member states varies considerably, but it must respect the EU's primacy law. Comparisons of legislation between member states reveal the marked differences in law.Women are significantly under-represented on the corporate boards of public limited companies in Europe. Legitimate questions need to be asked. Does the European Commission have the right to make a proposal for a directive allowing for parity on the boards of public limited companies in the EU? The reality is that the Commission does not have a solid approach in dealing with the issue of parity. As long as there is too much inconsistency between Member States, this leaves considerable room for further research. Legislation and governance law between member EU member states diverge considerably and demonstrate inconsistency with the legislation between them, resulting in little or no consensus in the interpretation of EU law. Or member states diverge with opposing interpretations of EU law, especially concerning sovereignty.National legal systems differ considerably in the way legislation allows for the appointment of board members and the notion of parity. A review of corporate governance matters concerning shareholders, the composition and appointment of board members corporate governance codes reveal the gap between member states. The research focus on parity by way of a comparison of the soft and hard laws of the member states.. The research upholds European law Article 157(3) Treaty of the Functioning on the European Union (TFEU), which is the fundamental principle of EU law and basis of gender equality and parity.The research will contribute to raising awareness of this issue through quota legislation and the question of parity on boards in public limited companies in the EU.
Issue: 2022UPASH012
Keywords: Board of directors; Comparative Law; Conseil d'administration; Corporate Governance; Droit comparé; Gender and parity; Genre et parité; Gouvernance des entreprises; Quotas; The European Union; Union européenne

The protection of the national labour force against foreign competition under labour migration laws and policies : a comparative analysis between the Democratic Republic of Congo and South Africa - Kamwimbi, Kasongo Theodore (University of South Africa, 2022)
Labour migration, which involves both labour immigration and labour emigration, refers to ‘the cross-border movement of people from a homeland to a location outside that homeland, with the purpose of taking up employment’.1 Labour migration has become an ever more important feature of the globalising world as it plays an important role and has a direct impact on African countries’ economies and societies. Recognising the significant benefits of labour migration to countries of origin and destination, the African Union urges African States to enact labour migration laws, regulations, and policies in a regular, transparent, and comprehensive manner at both continental and country levels. In this regard, many African countries have exercised their prerogative to regulate labour migration, which falls within each state’s sovereign discretion. By way of illustration, this thesis focuses on two specific countries, namely the Democratic Republic of Congo (DRC) and South Africa, which have regulated the employment of foreign-born workers. The two countries have established a legal and regulatory framework aimed at protecting the national labour force against foreign competition. The two countries have been selected for this study because they are comparable in many ways while differing as much as possible in terms of the institutional set-up of their migration systems and labour markets. In fact, this study seeks to compare the DRC’s and South Africa’s labour migration laws, regulations and policies, particularly how these legal and regulatory instruments effectively protect the national labour force against foreign competition. In this sense, the study explores the overall successes and challenges of these legislative and regulatory endeavours, while identifying the shortcomings and merits of the implementation of the laws and policies in the two countries.
Keywords: Congo (Democratic Republic); Contract of employment; Emigration and immigration law; Foreign workers; Labor laws and legislation; Labour market; Manpower policy; Migrant workers; South Africa

A comprehensive analysis of the law regulating equal pay in South Africa - Ebrahim, Shamier (University of South Africa, 2022)
The purpose of this thesis is as follows. Firstly, to identify the problems associated with the causes of action in section 6(4) of the EEA; the onus in section 11 of the EEA; the right to access pay related information; the grounds of justification in section 6(2) of the EEA and the Employment Equity Regulations; the equal pay provisions in sections 198A-198C of the LRA; and section 27 of the EEA. Secondly, to discuss and analyse the South African equal pay legal framework in order to provide answers and solutions to the research problems. Thirdly, to discuss and analyse the international legal framework regulating equal pay and the United Kingdom equal pay law in order to provide answers to the research questions to the extent and breadth called for. Fourthly, to summarise the answers to the research questions as sourced from South African law, international labour law and the United Kingdom equal pay law.
Keywords: Comparator; Equal pay claims; Equal pay for substantially the same work; Equal pay for the same work; Equal pay relating to non-standard (atypical) employees; Grounds of justification; Hypothetical comparator; Onus in section 11 of the EEA; Right to access pay-related information; Same employer; Section 27 of the EEA; Section 6(4) of the EEA; Sections 198A-198C of the LRA; Subordinate comparator; Terms and conditions of employment

Legal texts on trade facilitation: comparative analysis of the World Trade Organisation and the African Continental Free Trade Area - Shumba, Willie (University of South Africa, 2022)
Trade agreements are a common feature in international economic law as they govern trade relations between states. These agreements are anchored by a firm foundation of the requisite legal provisions to support trade. In this regard, the World Trade Organisation (WTO) and the African Continental Free Trade Area (AfCFTA) have each developed their own legal texts that acknowledge the significance of trade facilitation and would, when implemented, facilitate the movement of goods and services across international borders. The thesis was a comparative analysis of the legal texts on trade facilitation of the WTO and the AfCFTA whose aim was to identify the resemblances and divergences between the two. The WTO has a broader mandate of global trade and ensures that trade amongst its members is conducted in conformity with global rules. On the other hand, the AfCFTA is a trade agreement that has been negotiated by African member states pursuant to the political vision of the African Union (AU), and within the confines of WTO, specifically Article XXIV of GATT 1994. This research was therefore undertaken against the backdrop of these seemingly contradicting circumstances. The central research question for the study concerns the differences and similarities between the legal texts on trade facilitation of the WTO and the AfCFTA. The study was qualitative involving a desktop review of primary and secondary sources of data. Among others, the thesis finds that the AfCFTA complies with the strategic goals of the AU, and at the same time, complements the multilateral trading system of the WTO. The thesis concludes that while there are certain similarities, the legal texts on trade facilitation of the WTO and the AfCFTA are different. The inherent dissimilarities in the texts are not contrary to the principles of the WTO. The thesis contributes to scholarly literature in trade facilitation with respect to both the AfCFTA and the WTO. It also identifies new areas for further studies and provides the necessary groundwork. The study recommends some improvements that can be made to the respective legal texts on trade facilitation.
Keywords: AfCFTA; AfCFTA Agreement; African Continental Free Trade Area; Comparative analysis; Customs union; Free trade area; GATT; General Agreement on Tariffs and Trade; Global trade; International Trade; Legal texts; Multilateralism; Regional Economic Community; Regional Trade Agreements (RTAs); Regionalism; Trade Facilitation Agreement (TFA); Trade agreement; Trade facilitation; World Trade Organization

An evaluation of the strengths and weaknesses of South Africa’s corporate rescue regime as a potential benchmark for Uganda - Waiswa, Abudu Sallam (University of South Africa, 2022)
This thesis evaluates the strengths and weaknesses of the legal framework on corporate rescue in South Africa and Uganda. Although corporate rescue was initially not one of the objectives of insolvency law, it has now become the focus of modern insolvency law. South Africa became the first country to recognise the need to create a legal framework for rehabilitating financially distressed companies when it incorporated judicial management in the Companies Act of 1926. Judicial management was, however, not successful as a corporate rescue procedure. The South African policy makers however continued to explore ways through which financially distressed but viable companies could be saved from collapsing. This culminated into the introduction of business rescue in Chapter 6 of the Companies Act 71 of 2008. The study presents a detailed analysis of the strengths and weaknesses of the South African business rescue framework. It posits that unlike the Ugandan system, the South Africa legal regime reflects the principles of a modern and effective corporate rescue system. Whereas the government of Uganda attempted to embrace corporate rescue through the introduction of administration in the Insolvency Act 2011, the law is devoid of the internationally recognised features of a modern and effective business rescue framework. Administration has remained a white elephant in Uganda’s insolvency system, with liquidation continuing to be the predominant procedure used by both creditors and financially distressed companies. It is recommended that Uganda’s policy makers should benchmark the South African system to reform Uganda’s corporate rescue framework. This thesis is based on the law as at 31st of May 2022, found in the sources available in South Africa and Uganda.
Keywords: Bankruptcy; Business rescue; Corporate insolvency; Corporate insolvency law; Corporate reorganizations; Corporate rescue; Insolvency; Judicial management; Provisional administration; Rescue finance; South Africa; Uganda

Three Essays on Digital Platforms and Competition Policy - Yan, Jun (Université Toulouse 1 Capitole, 2022)
Cette thèse se compose de trois chapitres indépendants et examine différentes questions antitrust liées aux plateformes de gatekeeper. Le chapitre I explore le problème du verrouillage vertical dans les marchés bifaces. Dans le cadre des Accelerated Mobile Pages (AMP) de Google, le chapitre 2 examine la question de l'accès des plates-formes de contrôle d'accès aux données des utilisateurs professionnels. Le chapitre 3 se concentre sur le droit d'auteur numérique et étudie le comportement de Google consistant à utiliser le contenu des éditeurs pour afficher des réponses courtes sur les pages de résultats de recherche.Le premier chapitre examine comment l'intégration verticale d'une plate-forme monopolistique, qui se caractérise par des externalités de réseau bilatérales entre groupes, influe sur son incitation à s'engager dans le verrouillage en aval. Je me concentre sur un environnement où la plate-forme et les vendeurs en aval sont confrontés à l'incertitude quant aux gains du commerce au stade de la passation des marchés. Le choc aléatoire étant non contractile, la contractualisation crée des frictions qui faussent la structure tarifaire de la plateforme. En revanche, l'intégration verticale atténue ce problème en permettant à la plate-forme d'intégrer le choc aléatoire des prix à la consommation. En raison de l'interaction entre la friction des transactions et les externalités de réseau intergroupes, je trouve que l'intégration verticale pourrait réduire l'incitation de la plate-forme à la forclusion.Le deuxième chapitre est un travail conjoint avec Doh-Shin Jeon. Nous étudions comment l'adoption par les journaux d'AMP, un format de publication qui permet le chargement instantané de pages Web dans les navigateurs mobiles, modifie l'allocation des données et, par conséquent, les incitations des journaux à investir dans un journalisme de qualité. L'adoption d'AMP permet à Google d'obtenir des données sur les consommateurs à partir d'articles AMP et de les combiner avec d'autres sources de données sur les consommateurs pour améliorer le ciblage des publicités diffusées par Google sur d'autres sites Web. Même si une telle combinaison de données augmente l'efficacité statique, elle peut réduire l'efficacité dynamique lorsqu'elle diminue les revenus publicitaires par trafic de journal, réduisant ainsi la qualité du journalisme. Les journaux sont confrontés à un problème d'action collective car l'adoption de l'AMP par un journal génère des externalités négatives pour les autres journaux via le classement des recherches et la fuite de données. Google peut tirer parti de son pouvoir de marché dans la recherche et l'intermédiation publicitaire pour inciter les journaux à adopter AMP. Nous fournissons des recours politiques.Le troisième chapitre construit un modèle théorique de biens d'information divisibles pour examiner comment l'utilisation d'extraits par un moteur de recherche monopolistique impacte la consommation et la création de contenu. En affichant des extraits dans la zone de réponse sur les pages de résultats de recherche, le moteur de recherche dissocie les informations essentielles et les informations supplémentaires des articles. Elle crée donc deux effets opposés sur l'incitation des éditeurs à investir dans la qualité : l'effet de taille du marché et l'effet d'élasticité. Son impact sur le bien-être social est ambigu. D'une part, la boîte de réponse améliore l'efficacité de la recherche en offrant un accès plus large aux informations essentielles et en permettant aux consommateurs inframarginaux de substituer les informations essentielles à l'article complet. D'un autre côté, cela pourrait réduire le trafic sur le site Web, réduire les revenus publicitaires des éditeurs et les inciter à investir dans la qualité. J'examine les impacts des différentes politiques qui obligent le moteur de recherche à payer pour l'utilisation d'extraits.
Keywords: Antitrust law; Competencia; Competition Policy; Competition law; Concurrence; Concurrence (droit); Digital Platforms; Economie des médias; Google; Intellectual property; Marché biface; Media Economics; Online Advertising; Plateformes digitales; Propriedade intelectual; Propriété intellectuelle; Publicité en ligne; Technologies de l'information et de la communication – Aspect économique; Two-Sided Market

EU copyright reform : an institutional approach - Mangal, Natasha (Université de Strasbourg, 2022)
Cette thèse a pour objet d’étudier comment le dispositif institutionnel actuel pour l’adaptation du droit d’auteur dans l’Union européenne peut être reconsidéré afin de promouvoir le niveau de cohérence plus élevé dans les pratiques réglementaires des États membres, ainsi que dans l’intérêt de la promotion d’un corps de règles européennes plus dynamiques en la matière.À l’aide de l’outil normatif de l’analyse institutionnelle comparative, les dispositions institutionnelles actuelles sont examinées, en se concentrant sur la qualité de la participation des parties prenantes du droit d’auteur dans le système politique, le marché et les tribunaux. Des exemples d’institutions administratives du droit d’auteur dans certaines juridictions (États-Unis et Canada) sont analysés plus en détail, en tirant des conclusions sur leurs fonctions et leurs rôles dans leurs systèmes juridiques respectifs. Enfin, cette thèse propose plusieurs solutions politiques, y compris la possibilité d’envisager une nouvelle autorité au niveau de l’Union européenne pour le droit d’auteur. En fin de compte, la remise en question du statu quo institutionnel dans l’Union européenne peut révéler de nouvelles voies prometteuses pour développer les fonctions administratives, quasi judiciaires, d’observation et de conseil nécessaires à la gestion du droit d’auteur à l’ère du numérique.
Keywords: Analyse institutionnelle comparative; Comparative Institutional Analysis; Copyright; Digital Single Market; Droit de la propriété intellectuelle; Droit d’auteur; Droits d'auteur; Institutions; Intellectual property; Intellectual property law; Marché unique numérique; Union européenne

Performance and rarity of worker-owned firms : empirical evidence from France - Mirabel, Thibault (Université Paris 10, 2022)
This thesis compares the performance of worker-owned firms (WOFs) and conventional firms (CFs). These firms differ by their distribution of ownership rights and their mode of governance. In WOFs, the ultimate control is held by the suppliers of labor, whereas in CFs the ultimate control is held by the suppliers of capital. WOFs represent an implementation of democracy in firms and, as such, are likely to be immune to institutional harassment and socialwashing. WOFs have also been supported by citizens, politicians, and economists from across a wide ideological spectrum. Despite their attractiveness, WOFs represent a minute proportion of firms in our contemporary economies. This thesis seeks to bring new insights and stylized facts to better understand the rarity of WOFs. Chapter 1 studies how the interaction of the sunk costs of human capital and physical capital impacts the probability of WOF entry. I show that the likelihood of WOF entry is the highest when the sunk cost of human capital is dominant while the sunk cost of physical capital is negligible. Chapter 2 compares the survival patterns of WOFs and CFs. I show that WOFs survive longer than CFs regardless of whether they have different or similar entry resources, and that some entrepreneur and firm characteristics impact WOF and CF survival differently. Chapter 3 compares the survival patterns of WOFs distinguished by their entry mode (i.e., newly created, worker buyouts of sound CFs, worker buyouts of CFs in difficulty, and worker buyouts of nonprofit organizations). I show that any type of worker buyout survives longer than newly created WOFs. Overall, this thesis suggests that the rarity of WOFs is more likely to result from entry barriers specific to WOFs rather than from poor performance compared to CFs. Cette thèse compare la performance des coopératives de travailleurs (SCOPs) et des entreprises conventionnelles (ECs). Ces entreprises diffèrent par leur distribution des droits de propriété et leur mode de gouvernance. Au sein des SCOPs, les travailleurs ont le contrôle ultime de leur entreprise. Les SCOPs instituent la démocratie dans le monde économique et, à cet égard, furent et sont encore défendues par des économistes appartenant à une large palette idéologique. Malgré leur attractivité, les SCOPs représentent une fraction minuscule des entreprises dans le monde. Cette thèse entend apporter des éléments nouveaux pour comprendre la rareté des SCOPs. Le Chapitre 1 étudie comment l’interaction des coûts échoués en capital et en travail impacte la probabilité de créer une SCOP. Je montre que la probabilité de créer une SCOP est maximale lorsque le coût échoué en travail est dominant et que le coût échoué en capital négligeable. Le Chapitre 2 compare les profils de survie des SCOPs et des ECs. Je montre que les SCOPs survivent plus longtemps que les ECs indépendamment du fait que leurs ressources à l’entrée diffèrent ou non. Je montre aussi que certaines caractéristiques de l’entrepreneur différemment la survie des SCOPs et des ECs. Le Chapitre 3 compare les profils de survie des SCOPs en distinguant quatre modes d’entrée (les SCOPs nouvellement créées, les reprises d’entreprises saines, les reprises d’entreprises en difficulté et les reprises d’organisations à but non-lucratif). Je montre que les reprises en SCOPs survivent plus longtemps que les SCOPs nouvellement créées. Dans l’ensemble, cette thèse suggère que la rareté des SCOPs est due à des barrières à l’entrée spécifiques aux SCOPs plutôt qu’à leur prétendue moindre performance vis-à-vis des ECs.
Keywords: Coopératives; Coopératives ouvrières de production; Coûts échoués; Democracy; Efficacité de l'organisation; Entry mode; France; Mode de création; Participation à la gestion; Performance; Personnel; Scop; Sunk costs; Survie; Survival; Worker-owned firms; Études comparatives

An examination of the challenges posed by the internet economy for the South African income tax regime - Odhiambo, Oluoch Rodney (University of South Africa, 2022)
The way of doing business has changed significantly since the turn of this century due to the growth of internet technology and the global digital economy. This growth has reduced the importance traditionally attached to tangible assets and physical location in both commerce and taxation. This implies that any country that relies on physical presence to trigger tax liability in today’s digital economy may be forced to reconsider the relevance, effectiveness, and efficiency of its income tax legislation. This thesis postulates that South Africa’s income tax law and the international taxation principles it relies on in taxing cross-border and digital transactions have not grown in tandem with the changing landscape of today’s digital economy. The thesis contends that South Africa will not receive its fair share of tax from giant multinational enterprises such as Google, Facebook, and Amazon which operate and trade in the country, if it does not amend its income tax laws to address the challenges posed by the internet economy. In examining the challenges posed by the internet economy to South Africa’s income tax regime, the thesis commences in Chapter 2 by discussing the growth of the digital economy and its implications for South Africa’s income tax system. Chapter 3 offers a critical analysis of South Africa’s income tax laws and the international principles on which they rely in taxing the digital economy. Chapter 4 discusses the measures that South Africa’s government has taken to tax its digital economy, while Chapter 5 compares how the Organization for Economic Cooperation and Development (OECD), the European Union (EU), Kenya, India, and New Zealand have dealt with the issue of taxing the digital economy and the lessons to be learned from these jurisdictions. The thesis concludes in Chapter 6 by proposing recommendations that South Africa could consider to make its income tax regime more efficient and effective in taxing transactions that take place in today’s digitised economy.
Keywords: Cryptocurrency; Digital economy; Digital tax; E-commerce; E-signature; Electronic commerce; Formulary apportionment; Income tax; Internet industry; Signature électronique; Taxation; Virtual currency

The use of MASS in the context of International Law of the Sea - Mandrioli, Daniele (Università degli studi di Milano, 2022)
L'automatisation et la numérisation redéfinissent l'ergonomie des comportements humains. En se limitant au domaine maritime, les nouvelles technologies permettent d'automatiser entièrement l'activité traditionnelle de la navigation ; aujourd'hui, les navires peuvent être contrôlés depuis le rivage et l'intervention humaine dans la boucle de décision n'est plus nécessaire.Cette innovation disruptive offre de grandes opportunités pour l'industrie maritime. Intuitivement, les profits tirés du transport de marchandises et de personnes en mer peuvent être maximisés ; la réduction ou l'absence d'équipage à bord entraîne une réduction considérable des coûts pour les opérateurs (et pour les consommateurs), surtout en cette période historique marquée par la propagation mondiale du virus SARSCOV-2. En ce qui concerne la sécurité maritime, l'innovation que constitue le contrôle autonome réduit fortement le risque d'accidents dus à des erreurs humaines, qui sont à l'origine de la plupart des accidents maritimes. En ce qui concerne la protection de l'environnement marin, la navigation autonome peut en outre rendre le transport maritime plus durable.Pour ces raisons, les États et les entités privées financent plusieurs projets de développement de navires autonomes : au cours des dernières années, les premiers navires de surface autonomes (ci-après dénommés MASS) ont été testés et produits. En l'état actuel des connaissances, l'adoption de cette nouvelle technologie n'est plus un événement futuriste : plus d'un millier de MASS naviguent actuellement sur les océans du monde.Étant donné que l'activité humaine de la navigation est sujette à des changements, on peut se demander si les règles internationales qui la régissent sont d'une certaine manière remises en question par l'essor de l'automatisation.Habituellement, une nouvelle invention technologique s'accompagne de nombreuses questions réglementaires. D'une part, la loi est tenue de contrôler et de prévenir les conséquences involontaires découlant du recours à la nouvelle technologie. D'autre part, la loi est appelée à admettre et à autoriser son utilisation.Par conséquent, l'objectif de cette thèse est d'étudier les implications juridiques internationales découlant de l'utilisation croissante des moyens autonomes de transport maritime. En quelques mots, il s'agit ici d'aborder la question de savoir si et comment le recours à la technologie MASS a un impact sur le cadre juridique international préexistant qui régit l'exécution de la navigation et le contrôle de l'Etat sur celle-ci.Au cours des dernières années, ce sujet a suscité une attention croissante. En particulier, en 2019, le Comité de la sécurité maritime (CSM) de l'OMI a approuvé les "Directives provisoires pour les essais de navires autonomes de surface (MASS)". En outre, l'Organisation a très récemment achevé le "Regulatory Scoping Exercise on Maritime Autonomous Surface Ships" (ci-après RSE), qui avait débuté trois ans auparavant.La recherche proposée veut s'inscrire dans ce débat ouvert (et le dépasser) afin de fournir un panorama étendu des implications juridiques internationales émergeant de l'utilisation de l'automatisation et du contrôle dans le domaine maritime. Ce faisant, l'attention se concentrera sur trois blocs normatifs : les règles internationales sur la sécurité de la navigation (chapitre I), les règles internationales régissant l'attribution de la juridiction des États sur les navires (chapitre II) et les règles internationales traitant de l'assistance aux personnes trouvées en détresse en mer (chapitre III).
Keywords: Commande automatique; Droit de la mer; Droit maritime; Law of the Sea; Mass; Navires; Pilotes automatiques (navigation); Ships; Systèmes de guidage

Trade facilitation through border enforcement of Intellectual Property Rights: issues, concerns and possible remedies - Hossain, Syed Saifuddin (Macquarie University, 2022)
In the present era of rapid globalisation, countries are intrinsically integrated with each other by way of international trade to ensure optimal utilisation of their resources. Trade facilitation is now recognised as a key driving factor in determining export competitiveness of a country. Customs administrations, the frontier border agency responsible for regulating import and export of legitimate goods, are increasingly faced with the challenge of intellectual property rights (IPR) infringement. In addition to national governments, various international organisations have devised guidelines and tools to facilitate and empower Customs agencies in their fight against IPR infringement. In particular, the multilateral Agreement on Trade Related Aspects of Intellectual Property Rights (TRIPS) of the World Trade Organization (WTO) articulates a prescription for border enforcement of IPRs in Articles 51-60. In this backdrop, this thesis attempts to answer a very fundamental question: What are the implications of ‘Border Measures’, specified under the WTO TRIPS Agreement, for facilitating international trade? To this end, it critically examines the concepts of trade facilitation, TRIPS and IPR protection to highlight the links that connect them and the missing links that need to be established. Obligations to protect IPR under national and international laws are also scrutinised. Research shows that efforts by WTO, World Customs Organization (WCO) and World Intellectual Property Organization (WIPO) have been instrumental in this context. While policy planning at the national level should be the first priority, commitment by the advanced economies to support their less developed counterparts through technology transfer (TT) is of paramount importance. The thesis suggests that TRIPS-plus provisions, if implemented arbitrarily by developed countries, have the potential to undermine the interests of countries with resource constraints. In this context, the thesis analyses the effects and implications of the Trans-Pacific Partnership (TPP) and the Trans-Atlantic Trade and Investment Partnership (TTIP) agreements, and the Revised Kyoto Convention (RKC) for the border protection of IPRs. The thesis investigates the socio-economic impacts of IPR infringement and articulates strategies to be adopted and applied at individual, collective, business and government levels to stop trade and use of IPR infringed goods. Drawing on the analysis of the relevant WTO Articles, scrutiny of various border measures put in place by national governments and international bodies, and current state of play under the Doha Development Round (DDR), the thesis puts forward a set of short and long term policy recommendations for all relevant stakeholders. These inclusively include: (i) strengthening risk management procedures; (ii) cooperation and coordination at national and international levels; (iii) awareness raising initiatives; (iv) establishing advanced technologically driven border enforcement system; (v) empowering Customs with effective administrative authority; (vi) IP related technical capacity building within the Customs and business community; (vii) technology transfer to LDCs from developed countries; and (viii) LDC friendly dispute settlement process under the WTO.
Keywords: Border protection; Customs; IPR; Intellectual property; Intellectual property infringement; Intellectual property rights; Trade facilitation

The Economics of Trade, Innovation and the Technology Revolution - Tharwat, Ismaeel (Université Paris-Saclay, 2022)
Cette thèse étudie principalement l'impact du commerce international sur l'innovation, avec un accent particulier sur les pays en développement. Elle couvre également l'impact des retombées commerciales sur les inégalités de genre. Le chapitre 1 présente un aperçu de la littérature économique théorique et empirique récente traitant de l'effet de la concurrence des importations sur les résultats liés à l'innovation. Ce chapitre est divisé en quatre sections. Tout d'abord, un historique des brevets et des marques déposées en tant qu'indicateurs d'innovation est présenté. Deuxièmement, les mécanismes théoriques qui sous-tendent l'impact de la concurrence des importations sur l'innovation sont discutés. Troisièmement, une revue de la littérature des études empiriques récentes sur le commerce et l'innovation est résumée. Enfin, une analyse empirique est menée pour examiner l'impact de la concurrence des importations chinoises sur l'innovation, mesurée par l'activité de dépôt de brevet, dans les pays en développement.Le chapitre 2 est un exercice empirique qui examine l'impact de la concurrence des importations chinoises sur l'innovation, en utilisant une nouvelle mesure qui est le dépôt de brevet. L'étude utilise un ensemble de données de panel de 1995 à 2018 sur plus de 100 pays en développement. Le modèle empirique corrige l'endogénéité en utilisant une approche de variable instrumentale qui permet d'identifier la part du développement dû aux importations chinoises dans d'autres pays en développement. Les principales estimations trouvent un effet global décroissant de la concurrence des importations sur l'activité de dépôt de brevet. Les résultats de la variable instrumentale sont particulièrement robustes pour les demandes de brevet, mais pas pour les enregistrements. Cela suggère que la concurrence des importations affecte négativement les nouvelles innovations locales de produits ou de services dans les pays en développement.Enfin, le chapitre 3 aborde la question de l'impact des retombées du commerce international sur les normes d'égalité de genre. La majorité des études existantes documentent l'effet des épisodes de libéralisation sur les inégalités de genre. Celui des acteurs commerciaux, en revanche, a été largement ignoré. L'inégalité de genre au sein d'un pays est-elle affectée par ses partenaires commerciaux? Nous avons examiné cette question dans cet article en adoptant un modèle spatial du commerce entre 123 pays sur la période 1997-2013. Nous utilisons l'indice d'inégalité de genre pour capturer les tendances globales sur le genre au sein d'un pays. Nous avons ensuite désagrégé les échanges commerciaux au niveau produits afin d'identifier un canal technologique. Les résultats montrent que des normes d’égalité de genre plus élevées à l'étranger se répercutent, via les importations de produits de moyenne, haute technologie et minéraux, sur des normes d'égalité de genre plus élevées au niveau national. Ces résultats suggèrent qu'une révolution technologique affecte les entreprises, les ménages et les gouvernements en ayant un impact sur l'autonomisation des femmes.
Keywords: Brevets; Brevets d'invention; Economie du genre; Economie internationale; Gender Economics; Innovation; International Trade; Marques commerciales; Marques de commerce; Patents; Technologie; Technology; Trademarks; Économie de marché; Études sur le genre

The legal framework for multimodal transport in West Africa: the African Continental Free Trade Area in perspective - Osinuga, Damilola (World Maritime University, 2022)
This thesis examines how multimodal transport can play a role in achieving the objectives of the African Continental Free Trade Area (AfCFTA). The thesis argues that multimodal transport is cheaper compared with unimodal transportation. While there are a number of issues affecting the operationalisation of multimodal transport in Africa, this study considers, at its core, the legal regimes and other fragmented institutional and governance frameworks of multimodal transport in West Africa. The fragmentation of the legal framework governing multimodal transport leads to uncertainty and unforeseeability of the liability of parties involved in multimodal transport, consequently leading to increased legal costs. There is an undisputed view that for effective regional integration, which Africa is seeking to achieve through the establishment of the African Continental Free Trade Area, there is a need to eliminate all trade barriers. Trade barriers (tariff or non-tariff barriers) should be removed to improve competitiveness and reduce trade friction costs. In other words, to achieve the objectives of the African Continental Free Trade Area, it is essential that all unnecessary costs associated with trade are eliminated or reduced to the barest minimum. The process of doing this is called trade facilitation. This thesis looks at the impact of trade facilitation on regional integration and trade. This thesis’ original contribution to knowledge is that Africa’s regional integration process needs cost-effective transportation in order to achieve smooth market access, and multimodal transportation can provide the most cost-effective solution. However, the legal uncertainty and complexities that could potentially ensue from the use of multimodal transport make it unattractive to prospective users. Accordingly, actions must be taken to reduce legal ambiguity and create a system in which liability is foreseeable and predictable. This study reveals that the current legal framework is incomplete, unsatisfactory and, ultimately, leads to uncertainty. The thesis further contends that neither the option of freedom of contract nor improving the current system of various Economic Community of West African States (ECOWAS )member-states’ view of multimodal transport, can significantly improve the current fragmented system or deliver the needed certainty. Accordingly, the thesis proposes that a modified uniform system would help achieve the legal certainty needed for multimodal transport. The thesis finally submits that the ECOWAS should establish a legally binding, regional governance regime on multimodal transport and a majority of its member-states should ratify the instrument.

Foreign Bank Penetration, Institutional Structures and Banking Sector Stability in Sub-saharan Africa - Abeka, Mac Junior (University of Cape Coast, 2022)
Link broken
Keywords: Bank penetration; Banking sector; Sub-Saharan Africa

The rising role of China and Chinese enterprises in transnational labour law: Theoretical inquiries and case studies in the context of Chinese outward mining investment in Africa - Chen, Si (McGill University, 2022)
Transnational labour law scholarship has emerged over the past three decades. However, relatively limited scholarship has explored the role of actors from emerging market economies and the challenges and opportunities they have brought for achieving decent work in a globalized economy. This thesis addresses the research gap through an in-depth investigation into the role of actors from China in the dynamics of multi-level governance of labour rights in a globalized economy. Building on a multi-level, actor-centred and processual approach, this thesis argues that China and Chinese enterprises are playing a rising role in developing and shaping the dynamics of multi-level governance of labour rights in the global cobalt supply chain. Furthermore, the thesis suggests that actors from China have started challenging some unequal patterns of existing labour governance in the global cobalt supply chain and have demonstrated the potential to form a counterbalancing force to challenge the dominant role of actors from the global North. A multi-level governance framework has recently emerged and rapidly evolved in the global cobalt supply chain to eliminate child labour in the artisanal copper-cobalt mining sector in the Democratic Republic of the Congo. This framework is complex, pluralistic, and decentred. A wide range of state and non-state actors are developing various governance initiatives and shaping the dynamics of multi-level governance. Actors from China are playing a rising role in the global cobalt supply chain alongside a few other actors that have also provided proposals from the global South. Over the past decade, Chinese state agencies, nationwide industry associations and mining enterprises have proactively engaged in developing and shaping the multi-level governance framework to address governance deficits on decent work in the global cobalt supply chain. State agencies have developed various regulatory documents to enhance the social dimension of the Chinese regulatory framework for outward foreign direct investment. Nationwide industry associations have further conceptualized the term “corporate social responsibility” and have taken labour rights as key to the social responsibilities of Chinese enterprises operating overseas. Specifically, a Chinese nationwide industry association for the mining industry has developed comprehensive guidelines and initiatives to clarify and operationalize the labour component of social responsibilities in Chinese outward mining investment. The changing dynamics of multi-level governance have played a crucial role in shaping the private labour governance initiatives that Chinese mining enterprises are developing in the global cobalt supply chain. The contributions of this thesis are original, significant, and timely, given the notable research gaps on China and Chinese enterprises’ engagement with the dynamics of multi-level governance of labour rights in a globalized economy and the ongoing development of a multi-level governance framework in the global cobalt supply chain
Identifier: https://escholarship.mcgill.ca/concern/theses/7d2790853
Keywords: Chinese enterprise; Droit du travail; Investment in Africa; Labour law; Transnational labour law

Local Content Requirements in WTO Law: Between Free Trade and the Right to Development - De Lima Figueiredo, Natalia (Maastricht University; Universidade de São Paulo, 2022)
In the international arena, there is a strong rhetoric against a type of industrial policy measure called local content requirements (LCRs). They are often characterised, especially by developed countries, as protectionist measures. However, under certain circumstances, LCRs can have a central role in a country’s development process. Indeed, both developed and developing countries use them to boost their economies. Despite this developmental aspect of LCRs, WTO (World Trade Organization) rules restrict their use. The WTO Agreement, however, has a development dimension and WTO law is supposed to be read in light of the wider corpus of international law. The right to development, in turn, is a principle rooted in core human rights treaties, is consolidated in several instruments of soft law nature and could potentially play a role in the interpretation of WTO provisions. In this scenario, the thesis investigates if it is possible to further a development-oriented interpretation of WTO rules affecting LCRs so that those measures that incorporate genuine development goals are not considered a violation of WTO rules.
Keywords: Development; Free Trade; Human rights; Local content requirements (LCRs); WTO; World Trade Organization

Bank Bail-ins in International Investment Law - Duque-Cordero, Luciano (Universität Wien, 2022)
The global financial crisis led to the introduction of special resolution regimes for financial institutions. The most prominent innovation of these resolution regimes is the so-called bail-in tool, which allows regulators to recapitalise financial institutions by expropriating shareholders and creditors. This thesis analyses the conditions under which a hypothetical bail-in of a financial institution would constitute a compensable breach of international investment law. It identifies the issues that are most likely to be relevant if a bail-in were to be litigated before an investment arbitration tribunal. The thesis first addresses jurisdictional issues, in particular the question of whether bail-inable instruments can even be considered an investment in procedural terms. The analysis then continues to substantive standards of protection. It deals comprehensively with the question of expropriation and related issues such as compensation, the right to regulate, and causation. It concludes with possible violations of the fair and equitable treatment standard.
https://phaidra.univie.ac.at/detail/o:1417287
Keywords: Bail-in; Bank resolution; Expropriation; International Investment Law; Investments

Sanitary and phytosanitary measures as barriers to trade : a South African perspective - Joubert, Biandri (North-West University, 2022)
Sanitary and phytosanitary (SPS) measures are measures aimed at the protection of human, animal and plant life and health, within World Trade Organization (WTO) Member territories, from the risks associated with the introduction and spread of pests and diseases into such territories through trade. The WTO, through its Agreement on the Application of Sanitary and Phytosanitary Measures (WTO-SPS), guides the application of sanitary and phytosanitary measures and provides a set of guiding principles, rights and obligations applicable to Member States. Dispute resolution through the processes of the WTO is available to Members on a Member to Member level within a defined scope and on specific terms. Private parties who operate within the SPS chain at a national level, whether involved in import or export or neither, are dependent on solutions to barriers or disputes available to them through national legislation. In the absence of an enabling legal framework to facilitate aspects of trade such as certainty and continuity in standard setting, the basis of measures taken in science, transparency and legal recourse to resolving barriers or disputes arising, private parties are vulnerable to fluctuations in, for example, their country’s disease-free status. Private parties are also vulnerable to losing relevance as trading partners in periods of ongoing SPS events and to the loss of trust that trading partners have in the country’s ability to trade safely. These are matters that affect private parties who do not have legal recourse to the WTO dispute resolution procedures which are well within WTO concern as they are directly related to the purpose of SPS measures, the principles, rights and obligations on which they are based. Given the importance of agriculture and the increasing inseparability of international rights, obligations and principles in a field of WTO law such as SPS, the importance of a national legislative framework in as far as being the translator of such rights, obligations and principles into legally enforceable rights, obligations, principles, processes and procedures is significant. The rights, obligations, and principles of SPS measures apply to all products, processes and procedures that are within the scope of the agreement and may include at least 36 chapters of the harmonised tariff book. It is necessary to consider also that international trade, national trade and the associated rights, obligations, and principles of the WTO-SPS agreement interact with the social, political, and economic realities of the country within the countries to which the agreement applies. Therefore, researching some of the persistent challenges experienced by the red meat industry in South Africa prone to negative trade-related consequences during and after the outbreak of a notifiable disease, provides insight into the perception of the ability of the legislative framework to provide solutions to these consequences. This research applies a mixed methodology approach whereby qualitative research by means of semi-structured interviews was combined with doctrinal legal research and a quantitative content analysis using Rprogramming. The qualitative research focused on the role of legislation and the perspectives of selected actors in the red-meat industry, specifically in reference to the foot-and-mouth-disease (FMD) outbreaks and subsequent loss of disease-free status since 2019. The doctrinal legal analysis and content analysis focused on the SPS-related legislative framework. The combination of these methods provides a multi-perspective analysis of SPS measures as barriers to trade from a South African perspective and contributes to the mixed-methods turn in legal studies. The objective of this research is to identify and explore persistent challenges to the prevention and resolution of barriers or disputes connected to sanitary and phytosanitary (SPS) measures in the South African context. Ultimately, this research recommends potential practical solutions to the identified challenges with specific focus on SPS-related barriers or disputes that are beyond the strict terms of dispute resolution available through the World Trade Organization (WTO).
Keywords: AfCFTA; Barriers to trade; CADA; CAQDSA; Content analysis; Dispute resolution; FMD; NTB; OIE; Qualitative research; Rstudio; SADC; SPS; Sanitary and phytosanitary measures; WTO

Paradigm Shift in Investment Treaty Arbitration: Toward Stricter Control over the Qualifications and Conduct of Arbitrators - Kamalinejad, Hassan (University of Victoria, 2022)
There is a growing concern over the qualifications and social interactions of investment treaty arbitrators. The characteristics of this class of international adjudicators have significantly evolved over the past few decades. The contemporary arbitration panelist interacts within a broad and complex network of arbitration participants. Their patterns of social behavior both within the community of panelists and within the broader network of actors in arbitration proceedings have fundamentally reshaped the composition, dynamics and culture of the arbitration community. These new forms of relationships and patterns of conduct are new in the context of public international law. These have created unprecedented challenges to the investment treaty arbitration system. New manifestations of attributes and social behavior of panelists demonstrate inadequacies of the existing standards, rules and procedures that govern panelists. This study surveys problematic patterns of social behavior of investment treaty adjudicators and shows how certain instances of social behavior inevitably or potentially jeopardize the very foundations of the system. This research empirically examines the voting behavior of two distinct groups of party-appointed panelists, and the results reveal a relationship between appointments and the decision-making attitude of adjudicators. It further methodically maps the pool of ICSID panelists and answers the question ‘who are ICSID panelists?’ It reviews the evolution of the attributes of ICSID adjudicators, assesses the composition of the ICSID pool, and evaluates the social interactions of this group of investment treaty adjudicators. To address the challenges that investment treaty arbitration faces, a radical and multidimensional shift is occurring in the system. This transformation is directed towards greater control over the qualifications and conduct of adjudicators. These developments reconstruct the composition of the pool of adjudicators and influence how they interact with other actors in investment treaty arbitration proceedings. The ongoing reform progress indicates that the attributes and behavior of future investment treaty adjudicators would likely be different from the characteristics and conduct of the contemporary generation of panelists.
URI: http://hdl.handle.net/1828/14772
Keywords: Arbitrage; Arbitragem; Arbitration; Arbitrators; Code of conduct; ICSID; Impartiality; Investment treaties; Investment treaty arbitration; Investments; Permanent court system; Qualifications; State practice

Climate change and development : the global administrative law of the UNFCCC financial mechanism - Larrea, Gonzalo (European University Institute, 2022)
This research deals with the legal responsibility of states to provide climate finance to developing countries in order to facilitate climate mitigation and adaptation. The research demonstrates that the area of climate finance has not escaped globalization, where global actors operating at a level beyond the state (the UNFCCC and several Climate Funds) have increasingly taken over some of the climate finance functions previously performed by states. Against this backdrop, the thesis also examines the role of international bodies in providing climate finance, assesses to what extent these bodies are accountable to affected local stakeholders, and puts forward recommendations to foster increased accountability. The research project employs Global Administrative Law (GAL) as a normative framework for assessing and fostering accountability. This thesis is relevant, first and foremost, as an examination of the extent to which global climate finance is adequate for addressing climate change impacts in developing countries. To this end, it engages in a detailed analysis of the international legal framework for climate change and of the relevant financial instruments. It also engages in a normative evaluation of these instruments using the standards proposed by GAL. In keeping with this, the research gives substance and a better definition to these standards. As such, the thesis has the potential to contribute not only to the literature on climate finance, but also to the literature on GAL. It also sheds light on the relationship between climate finance and GAL, a topic that has been largely neglected in the academic literature so far.
Accepted: 2022-03-02T09:10:59Z
Keywords: Climate Change; Climatic changes; Environmental Law

Letters of credit and demand guarantees : a legal study on the impact of targeted financial sanctions from a South African perspective - Lupton, Cayle Selwyn (University of Johannesburg, 2022)
The purpose of this study is to provide a legal analysis of the impact of targeted financial sanctions on letters of credit and demand guarantees. The letter of credit is an important method of payment used in international trade. The demand guarantee plays a significant role as an instrument of security in commercial transactions. In their simplest form both instruments constitute an undertaking by a bank to pay a beneficiary against delivery of certain stipulated documents. Letters of credit and demand guarantees are known to be reliable and provide a considerable measure of certainty and predictability to the underlying transaction. Consequently, they have been described as the “lifeblood of international commerce”. Targeted financial sanctions entail assets freezing and prohibitions to prevent funds or other assets from being made available, directly or indirectly, for the benefit of designated individuals and entities. Endorsed by the United Nations and implemented by the vast majority of jurisdictions around the world, targeted financial sanctions are increasingly being used to combat financial crime, including money laundering, terrorism financing and weapon proliferation financing. Banks play a critical role in financial crime prevention and detection. Hence they have been identified as institutions that must comply with targeted financial sanctions. The relationship between targeted financial sanctions and letters of credit and demand guarantees has generally not been well documented. It is hoped, therefore, that this study will make a meaningful contribution to the jurisprudence on letters of credit and demand guarantees. In investigating the impact of targeted financial sanctions, the study can be categorised into three parts. Part one investigates a bank’s compliance with domestic targeted financial sanctions. The chief findings of the study in this regard are that banks are under a legal obligation to comply with sanctions and, as a result, a bank that refuses to perform its contractual obligations under a letter of credit or demand guarantee may have a defence in law. In South African law the bank can raise the so-called defence of legal impossibility of performance to resist a claim for, or potential litigation in respect of, payment. Part two investigates a bank’s compliance with foreign targeted financial sanctions. Because compliance in this regard has no (legal) basis, the bank may conceivably be sued by the beneficiary for payment on the basis of breach of contract. Part three investigates problematic documentary practices that banks have adopted or conceivably may adopt to manage their sanctions risk exposure. In this regard, attention is given to so-called sanctions clauses and other non-documentary conditions. The issue of unjustified amendments by the beneficiary for the purposes of sanctions evasion is also considered in part three. The general conclusion arrived at is that by interfering with payment, targeted financial sanctions render letters of credit and demand guarantees unreliable, thereby having the effect of reducing their value to international trade and commerce. The author proposes certain recommendations and initiatives aimed at mitigating the impact of targeted financial sanctions on credits and guarantees. Key terms: letters of credit; demand guarantees; financial crime; sanctions evasion; targeted financial sanctions; compliance; banks; due diligence; payment; reimbursement; credits; guarantees.
Keywords: Banks; Compliance; Credits; Demand guarantees; Due diligence; Financial crime; Guarantees; Letters of credit; Payment; Reimbursement; Sanctions evasion; Targeted financial sanctions

Airport Charges Regulation: A Private Law Approach - Mei, Di (McGill University, 2022)
This thesis explores the regulation of airport charges, which is an important but marginalised topic. It particularly examines how private law instruments can play a role in the regulatory process. Airports used to be subject to traditional regulation, which operates in a command-and-control mode. As the airport industry becomes increasingly complicated, traditional regulation seems problematic. First, the method that is associated with traditional regulation to draw a line between regulated and unregulated airports has downsides. Second, the international regulatory framework on airport charges lacks binding rules. This suggests that traditional regulation is not the best niche for airport charges regulation. Third, good regulation needs independent regulatory bodies, which are hard to achieve in practice.In this context, this thesis argues that a private law approach can serve as a more flexible and effective way to regulate airport charges. There are two instruments under this overarching approach. First, contracts can be adopted to incorporate airport charges regulations. Second, robust corporate governance generates the effect of good regulation. This is an interdisciplinary work that has engaged air law, contract law, corporate law, competition law, and aviation business and management. It also employs the method of case studies. Chapter 4 examines the regulation of airport charges in the UK, Canada, and India. The three case studies demonstrate that private law instruments have been implicitly implemented to different degrees in these countries. These demonstrate the feasibility of applying private ordering in the regulatory process. I also look into the regulation of countries and regions including Australia, Ireland, the EU, and Germany throughout this thesis. This study also examines a specific sector of airport charges, namely, charges for ground-handling services. This sector possesses a unique feature in that it is between aeronautical and non-aeronautical services. A private law approach can also be adopted in the regulation of charges relating to ground-handling services. Additionally, ICAO as an important international organisation governing international air transport can also contribute to a private law approach of airport charges through its soft-law making function. This thesis aims to shed light on a private law approach, as an innovative regulatory mechanism, to airport charges. That said, regulation by this approach and traditional regulation are not contradictory but can cooperate to an extent, depending on how much power one wants to give to private ordering
Identifier: https://escholarship.mcgill.ca/concern/theses/8910k0504
Keywords: Airport; Regulation

Articulating clearer fair and equitable treatment clauses within Tanzania’s international investment agreements: correcting the disparity between host state and international investor interests - Ntangeki, Joanitha (Canterbury Christ Church University, 2022)
International Investment Agreements seek to promote foreign investment whilst protecting foreign investors. Despite the goal of International Investment Agreements being to secure parity between the interests of the host State and the foreign investor, there has been consequential disparity in the protection of the interests of both parties. Notably, the host State is susceptible to disadvantage. This research examines the extent to which International Investment Agreements in Tanzania have facilitated this disparity. In particular, the research evaluates the inclusion of fair and equitable treatment provisions in Tanzania’s International Investment Agreements and the extent to which fair and equitable treatment provisions have in some way facilitated this disparity. The research examines systematically the fair and equitable treatment provisions contained in twenty IIAs signed by Tanzania between 1965 and 2013 (eleven of which are still in force). The research takes a comparative approach in evaluating and contrasting the Tanzanian provisions with other fair and equitable treatment clauses in IIAs signed by India, Morocco and the Netherland. The Tanzanian provisions are vague and non-uniform in comparison. The research is situated in the broader context of national sovereignty and the relationship between Tanzania and its foreign investors under international law. The substance of the analysis centres on foreign investors in the mining sector in Tanzania and the extent to which these investors have sought to take advantage of the fair and equitable treatment clauses in the IIAs in order to pursue their activities to the detriment of local populations. The research evidences the negative impact of their claims that changes in government policy (often aimed at benefiting citizens) amount to unfair treatment of the foreign investor. This has a significant impact on the ability of the government to develop its policies around sustainable development, environmental protection and the guarantee of human rights of the citizens of the host State. The research demonstrates that a clearer and fuller articulation of fair and equitable treatment clauses within Tanzania’s IIAs can act as a corrective to the disparity between the host State and the international investor. This requires that IIAs are drafted to include an exhaustive and full list of the State’s obligations towards the foreign investor so as to limit foreign investor claims against the host State. The impact of not doing so has grave implications for the rights of the citizens of Tanzania and unnecessarily tips the balance of power in favour of the foreign investor and away from the host State. This undermines the ability of the host State to assert its sovereignty within its own borders.
Permalink: https://repository.canterbury.ac.uk/item/9714v/articulating-clearer-fair-and-equitable-treatment-clauses-within-tanzania-s-international-investment-agreements-correcting-the-disparity-between-host-state-and-international-investor-interests
Keywords: Foreign investment; International investment; Investor interest; Tanzania